Assessing Phototoxicity in a Mammalian Cell Line: How Low Levels of Blue Light Affect Motility in PC3 Cells - Alghamdi, Rana A.; Exposito-Rodriguez, Marino; Mullineaux, Philip M.; Brooke, Greg N.; Laissue, Philippe P. (Frontiers in Cell and Developmental Biology, 2021)
Phototoxicity is a significant constraint for live cell fluorescence microscopy. Excessive excitation light intensities change the homeostasis of the observed cells. Erroneous and misleading conclusions may be the problematic consequence of observing such light-induced pathophysiology. In this study, we assess the effect of blue light, as commonly used for GFP and YFP excitation, on a motile mammalian cell line. Tracking PC3 cells at different light doses and intensities, we show how motility can be used to reliably assess subtle positive and negative effects of illumination. We further show that the effects are a factor of intensity rather than light dose. Mitotic delay was not a sensitive indicator of phototoxicity. For early detection of the effect of blue light, we analysed the expression of genes involved in oxidative stress. This study addresses the need for relatively simple and sensitive methods to establish a dose-response curve for phototoxicity in mammalian cell line models. We conclude with a working model for phototoxicity and recommendations for its assessment.